A Pragmatic Approach to the Perioperative Management of Parkinson's Disease. (22nd May 2021) - Lenka, Abhishek; Mittal, Shivam Om; Lamotte, Guillaume; Pagan, Fernando Luis
ABSTRACT: Patients with Parkinson's disease (PD) may undergo several elective and emergency surgeries. Motor fluctuations, the presence of a wide range of non-motor symptoms (NMS), and the use of several medications, often not limited to dopaminergic agents, make the perioperative management of PD challenging. However, the literature on perioperative management of PD is sparse. In this descriptive review article, we comprehensively discuss the issues in the pre-, intra-, and postoperative phases which may negatively affect the PD patients and discuss the approach to their prevention and management. The major preoperative challenges include accurate medication reconciliation and administration of the dopaminergic medications during the nil per os (NPO) state. While the former can be addressed with staff education and PD-specific admission protocols, knowledge of non-oral formulations of dopaminergic agents (apomorphine, inhalational levodopa, and rotigotine transdermal patch) is the key to the management of the Parkinsonian symptoms in NPO state. Deep brain stimulation (DBS) devices should be turned off to avert potential electromagnetic interference with surgical appliances. Choosing the appropriate anesthesia and avoiding and managing respiratory issues and dysautonomia are the major intraoperative challenges. Timely reinitiation of dopaminergic medications, adequate management of pain, nausea, and vomiting, and prevention of postoperative infections and delirium are the postoperative challenges. Overall, a multidisciplinary approach is pivotal to prevent and manage the perioperative complications in PD. Administration of anti-Parkinson medications during NPO state, prevention of anesthesia-related complications, and timely rehabilitation remain the key to healthy surgical outcomes.